(untitled) (The Eurasia Proceedings of Educational and Social Sciences, 2018)
Although studies suggest that metacognitive strategy instruction can promote increased problem solving in the classroom, little evidence has been collected that directly probes the role of metacognition in problem solving. This study examined high school students’ metacognition and physical problem solving skills and looked for a relationship between the two. A correlational research design was carried out for this research. Participants of the study were eleventh graders studying in an urban all-boys school. The Metacognition Awareness Inventory was administered to determine the students’ metacognition. Physical Problem Solving Assessment Inventory was used to assess the participants’ problem solving strategies. Results showed that the students’ metacognitive awareness level was close to high. Their knowledge about cognition was higher than their regulation of cognition. Additionally, the students’ physical problem solving strategies were little. Results also presented that the more metacognitive awareness the students had the more knowledge of reading they had. Pearson correlation coefficient analyses indicated a significant medium level positive relationship between the students’ metacognitive awareness and their physical problem solving strategies.